Utilization of fluoroform for difluoromethylation in continuous flow: a concise synthesis of α-difluoromethyl-amino acids. Issue 1 (9th November 2017) - Köckinger, Manuel; Ciaglia, Tanja; Bersier, Michael; Hanselmann, Paul; Gutmann, Bernhard; Kappe, C. Oliver
Abstract : Difluoromethylated esters, malonates and amino acids (including the drug eflornithine) are obtained by a gas–liquid continuous flow protocol employing the abundant waste product fluoroform as an atom-efficient reagent. Abstract : Fluoroform (CHF3 ) can be considered as an ideal reagent for difluoromethylation reactions. However, due to the low reactivity of fluoroform, only very few applications have been reported so far. Herein we report a continuous flow difluoromethylation protocol on sp 3 carbons employing fluoroform as a reagent. The protocol is applicable for the direct C α -difluoromethylation of protected α-amino acids, and enables a highly atom efficient synthesis of the active pharmaceutical ingredient eflornithine.